THE EFFECT OF SUPPLEMENTING IN PREGNANT MOTHERS ON LOW BORN BABY BABY IN COUPLIC CLINICS: PENGARUH PEMBERIAN SUPLEMEN PADA IBU HAMIL TERHADAP BAYI BERAT LAHIR RENDAH DI KLINIK PASUTRI - Dewi Dewi Nopitasari; Tri Tri Maghfiroh (Jurnal Ilmiah Wijaya, 2018)
Background of the study : According to data from Indonesia Demographic and Health Survey (IDHS) in 2012, Infant mortality rate (IMR) of 32 deaths / 1,000 live births. The low level of awareness among pregnant women in taking supplements during pregnancy can lead to a variety of impacts for both the mother and baby, including the baby is born with low birth weight (LBW). Objective : Knowing Effect of Supplements On Pregnant Women Against Low Birth Weight Babies in Clinic Pasutri 2018th. Methods : This type of research is an analytical study using cross sectional approach. Respondents in this study were mothers with babies in Clinic Pasutri, the number of 81 respondents. The sampling technique in this study using random sampling techniques. The research instrument was a questionnaire and medical record that is presented in tabular form and processed using SPSS 16.0 type. Result : From 81 respondens obtained maternal pregnancy supplements during pregnancy as many as 53 people or about 65.4% with an incidence rate of low birth weight babies as much as 18 or about 22.2%, while women who did not take supplements of pregnancy by 28 people, or approximately 34.6% LBW incidence rate of about 17 babies, or about 21.0% of total births. Conclusion: There is a relationship effect of supplementation in pregnant women on low birth weight babies in BPS K, Bogor. This is evidenced by the results of P - value is 0.021, which means the value of P - value less than α 0.05.